Subjective cognitive complaints across the adult life span: a 14-year analysis of trends and associations using the 1993, 2000 and 2007 English Psychiatric Morbidity Surveys. Issue 9 (July 2014) - Begum, A.; Dewey, M.; Hassiotis, A.; Prince, M.; Wessely, S.; Stewart, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Cognitive complaints are common in all age groups but most often researched in old age. We aimed to investigate prevalences and time trends over 14 years of subjective memory complaints (SMC) and subjective concentration complaints (SCC) in adults and investigate associations with mood disorders and cognitive function. Method Data from three English national mental health surveys carried out in 1993, 2000 and 2007 were analysed. SMC and SCC were measured using the Clinical Interview Schedule – Revised and cognitive function using the modified Telephone Interview for Cognitive Status. Results Both SMC and SCC increased up to middle age and then declined, followed by a second rise in the very oldest age groups. Age-specific prevalence of both increased across survey years but relationships with mental health and cognitive outcomes were relatively stable. Conclusions Cognitive complaints are most common in middle age and have become more prevalent over time.